Perancangan Sistem Informasi Akademik Dengan Menggunakan Metode Rapid Application Development (RAD) Berbasis Webiste Studi Kasus di SMP NU Medan - Gilang Dwi Fahri Harahap; Muhammad Khaibar Putra Adithia; Demonius Sarumaha; Mardiah (Jurnal Ilmu Komputer dan Sistem Informasi, 2024)
The education system in Indonesia is experiencing rapid development characterised by an increase in the number of schools, students, and the complexity of the teaching and learning process. To manage academic data that includes information on students, teachers, grades, attendance, and class schedules, schools need to improve the quality of their services. Education is an important aspect of the country's development, and in this context, Academic Information System (AIS) plays a vital role in supporting administration and management in educational institutions. This research focuses on SMP NU Medan, where the need for an efficient and integrated AIS is increasingly urgent to improve the quality of education services. With the rapid development of information technology, the Rapid Application Development (RAD) method is the right choice because it allows rapid and iterative application development. In addition, Web-based AIS provides wide accessibility for education stakeholders, including making it easier for prospective students to access information and register online. The case study at SMP NU Medan provides a strong foundation for this research by identifying specific needs and coming up with solutions that are relevant and can be implemented immediately. This research aims to design, implement, and evaluate a Web-based AIS using the RAD method, so that it can make a positive contribution in improving the efficiency, accuracy, and quality of service of the school.